Green Synthesis Of Silver Particles At Room Temperature Using Gynura Procumbens Aqueous Extract - Hat, Khairunisa (Universiti Sains Malaysia, 2017)
This study focuses on biosynthesis of silver nanoparticles using Gynura Procumbens leaf extract as reducing and stabilizing agents. Aqueous silver ions when exposed to plant leaf extract were reduced and resulted in a colour change indicating the formation of silver nanoparticles. The synthesized silver nanoparticles were characterized by UV-Vis Spectroscopy, Fourier Transform Infra-red Spectroscopy (FT-IR), Transmission Electron Microscopy (TEM) and Zeta Potential Analysis techniques. The UV-Vis spectrum of aqueous medium containing silver nanoparticles as a function of time of reaction showed gradually increasing surface Plasmon resonance peak intensity at 449 nm to 452 nm of silver. A few parameters for examples volume ratio of plant extract to silver nitrate, plant extract concentration, silver nitrate concentration are also have been studied and shows the same range of wavelength at maximum absorption. The highest absorbance, 1.75 was obtained after 4 days using 12mM silver nitrate react with 5% plant extract in ratio of 1:50. Zeta Potential Analysis proves silver nanoparticles’s stability by having the value -40mV. FTIR spectroscopy analysis showed that silver nanoparticles are capped by various protein molecules. Transmission Electron Microscopy confirmed the spherical shape of nanoparticles.